Business Interruption Insurance, Pandemics, And a Very U.K. Story of Dispute Resolution. Issue 6 (29th May 2021) - Samuel, Adam
Abstract : The United Kingdom has a dispute resolution problem that stems from the pandemic that cannot be entirely unique to Great Britain. Providers of business interruption insurance have been less happy about paying out on policies taken out by businesses in view of the extreme nature of the pandemic.